2018
DOI: 10.1002/ppsc.201800105
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and Graphene‐Based Materials in Biomedical Science

Abstract: Graphene and its composite materials are very important in many disciplines of science and have been used enormously by researchers since their discovery in 2004. These are a new group of compounds, and are also wonderful model systems for quantum behavior studies. Their properties like exceptional conductivity, biocompatibility, surface area, mechanical strength, and thermal properties make them rising stars in the scientific community. Graphene and its composite compounds are utilized widely in different med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 371 publications
1
8
0
Order By: Relevance
“…New kinds of nanomaterials are studied recently for developing sensors; among these graphene based sensors got more attention due to exceptional properties like, high electrical conductivity, mechanical strength, and molecular barrier abilities . These striking features of graphene have made it an active platform for engineering metal nanoparticles on its surface .…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…New kinds of nanomaterials are studied recently for developing sensors; among these graphene based sensors got more attention due to exceptional properties like, high electrical conductivity, mechanical strength, and molecular barrier abilities . These striking features of graphene have made it an active platform for engineering metal nanoparticles on its surface .…”
Section: Introductionsupporting
confidence: 52%
“…These striking features of graphene have made it an active platform for engineering metal nanoparticles on its surface . Along with graphene, recently graphene‐based nanocomposites involving nanoparticle and conducting polymers have gained considerable recognition due to improved electrocatalytical activities and have been reviewed extensively for electrochemical biosensing applications . Interestingly, silver nanoparticles decorated graphene composites electrodes have shown excellent electrochemical activities towards sensing of biological compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene-based materials (GBM), a new family of nanomaterials, have attracted a lot of attention in the scientific community, with increasing interest and potential in biomedical applications [24][25][26][27][28]. The antibacterial effect of these materials was first explored in suspension in 2010 by Hu et al [29] and since then increasing number of studies have described GBM as having antibacterial activity, making them strong candidates for antimicrobial applications [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The observed order can be further explained by the amount of oxygen functional groups present. It has been reported that sp2 carbon and sp3 carbon binding energy of graphene oxide from the deconvoluted C1s peak appear in the range of 284.6 eV ± 0.3 eV, whereas carbon-bound oxygen functional groups appear at higher energy due to oxygen's electronegativity [14,15]. In addition, the B1s peak of B-rGO was observed at 193.3 eV; the N1s peak of the N-rGO was seen at 400.1 eV, while a small F1s peak of the F-GO appeared at 692.7 eV.…”
Section: Surface Characterizationmentioning
confidence: 99%
“…The structure of graphene includes a single layer of sp2-hybridized hexagonal lattices that form honeycomb structures with a high surface area, which are both electronically and thermally conductive [9]. Graphene oxide (GO) synthesized from graphite contains abundant oxygen functional groups, including hydroxyl, carboxylic acids, and epoxy groups, which demonstrate good catalytic activities, particularly for the oxidation of organic molecules [12][13][14][15]. However, the presence of oxygen groups disrupts the sp2 bonds of carbon rings, thereby lowering conductivity.…”
mentioning
confidence: 99%